Reduced serum content and increased matrix stiffness promote the cardiac myofibroblast transition in 3D collagen matrices. - Galie, Peter A. (2011)
INTRODUCTION: The fibroblast-myofibroblast transition is an important event in the development of cardiac fibrosis and scar formation initiated after myocardial ischemia. The goals of the present study were to better understand the contribution of environmental factors to this transition and determine whether myofibroblasts provide equally important feedback to the surrounding environment. METHODS: The influence of matrix stiffness and serum concentration on the myofibroblast transition was assessed by measuring message levels of a panel of cardiac fibroblast phenotype markers using quantitative rtPCR. Cell-mediated gel compaction measured the influence of environmental factors on cardiac fibroblast contractility. Immunohistochemistry characterized α-SMA expression and cell morphology, while static and dynamic compression testing evaluated the effect of the cell response on the mechanical properties of the cell-seeded collagen hydrogels. RESULTS: Both reduced serum content and increased matrix stiffness contributed to the myofibroblast transition, as indicated by contractile compaction of the gels, increased message levels of col3α1 and α-SMA, and a less stellate morphology. However, the effects of serum and matrix stiffness were not additive. Mechanical testing indicated the cell-seeded gels became less viscoelastic with time, and that reduced serum content also increased the initial elastic properties of the gel. CONCLUSIONS: The results suggest that reduced serum and increased matrix stiffness promote the myofibroblast phenotype in the myocardium. This transition both enhances and is promoted by matrix stiffness, indicating the presence of positive feedback that may contribute to the pathogenesis of cardiac fibrosis. SUMMARY: Lower serum content and increased matrix stiffness accelerated the transition of cardiac fibroblasts seeded in collagen hydrogels to a myofibroblast phenotype, though their effects were not additive. Reduced serum also affected mechanical properties of the hydrogels, suggesting that the myofibroblast transition both augments and is accelerated by matrix stiffness. This positive feedback may contribute to cardiac fibrosis pathogenesis.